Use of Multiple Perineural Adjuncts in Quadratus Lumborum Block and Lumbosacral Plexus Block to Provide Anesthesia for Hip Fracture Repair: A Case Report - Lee, LL; Chan, A; Wong, JTK (Archives of Clinical and Medical Case Reports, 2022)
Abstract not available in the source database.